Kontribusi Kondisi Lingkungan, Kelengkapan Fasilitas Dan Motivasi Terhadap Kedisiplinan Belajar Di SMP N 1 Pulokulon - Grobogan - Triwahyuni, Susheni; , Prof. Dr. Sutama, M.Pd; , Dewi Candraningrum, Ph.D (2014)
The objectives of this research are to analyze: 1)the contribution of environment condition to study, completeness of facilities to study and learning motivation toward the students' learning discipline of the eight grade students of SMP N 1 Pulokulon. 2) the contribution of learning environment condition toward the students' learning discipline of the eight grade students of SMP N 1 Pulokulon. 3) the contribution of the completeness of facilities to study toward the students' learning discipline of the eigth grade students of SMP N 1 Pulokulon. 4) the contribution of learning motivation toward the students' learning discipline of the eigth grade students of SMP N 1 Pulokulon. The kind of this research is quantitative research. The research was conducted at SMP N 1 Pulokulon 2012/2013 academic year, with the population are all of the the eigth grade student. The all population are taken 75 respondents as the research sample with random sampling technique. Techniques of data collection used questionnaires. Technique of analyzing dataused multiple linear regression analysis, accuracy test model, accuracy test estimation parameter (t test), donations predictor and classical assumption. The results of this study state that : 1) The condition of the environment, complete facilities and motivation simultaneously have contributed to student discipline SMP N 1 Pulokulon. This is indicated by the value of significant level 0.009 < 0.05 and the effective contribution of 38.8 %. 2)The test results in partial environmental conditions showed a significant effect on learning discipline. The results of the ttest = 2.182, so that ttest > 2 then Ho is rejected, meaning that there is a significant effect between the variable environmental conditions for learning discipline. 3 ) The test results in partial, complete facilities showed no significant impact on student learning discipline. The results of the ttest = 1.650, so that ttest < 2 then Ho is accepted, it means there is no significant relationship between the variables complete facilities to learn discipline. 4) The test results in partial motivation showed a significant effect on student learning discipline. The results of the ttest = 2.180,so ttest > 2 then Ho is rejected, meaning that there is significant influence between the variables of motivation to learn discipline.